The Music Learner Voice: A Systematic Literature Review and Framework - Després, Jean-Philippe; Dubé, Francis (Frontiers in Education, 2020)
Since approximately 30 years, we are witnessing a re-emergent interest in learner voice from researchers, teachers, policymakers, and students themselves. This widespread movement foreshadows the potential for a shift of paradigm from a unilateral top-down directivity to an inclusive and dialogical decision-making process in school systems. Youth voice is crucial to reimagine education from a global, multi-stakeholder perspective, which can foster student engagement and promote meaningful learning experience. While the interest on the learner voice has burgeoned recently in the field of music education, the body of literature in this field is still relatively small, and its impact in the classroom and policies is limited. That said, a few research studies have been led to study specifically the learner voice in both in- and out-of-school contexts. However, so far, no systematic attempt to integrate these findings into a broader framework, depicting the diversity and the commonalities of the young learner voice in music education, has been made. To bridge this gap, we realize a systematic literature review of the research studies that are capturing the essence of young music learner voice, a corpus mostly comprised of narrative and storytelling studies. A thematic analysis is carried out to explore how young music learners describe their own musical experiences and meaning-making in informal and formal musical contexts. The results emerging from this systematic literature review are organized into a framework representing young learners’ perspectives on what they like and dislike about their musical experience. Practical implications resulting from this analysis are proposed for innovative pedagogical approaches and policies in music education, where the learner voice is inclusively engaged into a dialogical decision-making process. Finally, avenues for promoting a more significant inclusion of learner voice in music education and research are also explored.